Population Genetics of Phlebotomus papatasi from Endemic and Nonendemic Areas for Zoonotic Cutaneous Leishmaniasis in Morocco, as Revealed by Cytochrome Oxidase Gene Subunit I Sequencing - Souad Guernaoui; Omar Hamarsheh; Deborah Garcia; Didier Fontenille; Denis Sereno (Microorganisms, 2020)
Zoonotic cutaneous leishmaniasis (ZCL) caused by Leishmania major Yakimoff & Shokhor and transmitted by Phlebotomus papatasi (Scopoli) is a public health concern in Morocco. The disease is endemic mainly in pre-Saharan regions on the southern slope of the High Atlas Mountains. The northern slope of the High Atlas Mountains and the arid plains of central Morocco remain non-endemic and are currently considered high risk for ZCL. Here we investigate and compare the population genetic structure of P. papatasi populations sampled in various habitats in historical foci and non-endemic ZCL areas. A fragment of the mtDNA cytochrome oxidase I (COI) gene was amplified and sequenced in 59 individuals from 10 P. papatasi populations. Haplotype diversity was probed, a median-joining network was generated (FST) and molecular variance (AMOVA) were analyzed. Overall, we identified 28 haplotypes with 32 distinct segregating sites, of which seven are parsimony informative. The rate of private haplotypes was high; 20 haplotypes (71.4%) are private ones and exclusive to a single population. The phylogenetic tree and the network reconstructed highlight a genetic structuration of these populations in two well defined groups: Ouarzazate (or endemic areas) and Non-Ouarzazate (or nonendemic areas). These groups are separated by the High Atlas Mountains. Overall, our study highlights differences in terms of population genetics between ZCL endemic and non-endemic areas. To what extent such differences would impact the transmission of L. major by natural P. papatasi population remains to be investigated.